9(2-j)+3(5+2j)=2(7-2j)-4(4j-1)

Simple and best practice solution for 9(2-j)+3(5+2j)=2(7-2j)-4(4j-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(2-j)+3(5+2j)=2(7-2j)-4(4j-1) equation:


Simplifying
9(2 + -1j) + 3(5 + 2j) = 2(7 + -2j) + -4(4j + -1)
(2 * 9 + -1j * 9) + 3(5 + 2j) = 2(7 + -2j) + -4(4j + -1)
(18 + -9j) + 3(5 + 2j) = 2(7 + -2j) + -4(4j + -1)
18 + -9j + (5 * 3 + 2j * 3) = 2(7 + -2j) + -4(4j + -1)
18 + -9j + (15 + 6j) = 2(7 + -2j) + -4(4j + -1)

Reorder the terms:
18 + 15 + -9j + 6j = 2(7 + -2j) + -4(4j + -1)

Combine like terms: 18 + 15 = 33
33 + -9j + 6j = 2(7 + -2j) + -4(4j + -1)

Combine like terms: -9j + 6j = -3j
33 + -3j = 2(7 + -2j) + -4(4j + -1)
33 + -3j = (7 * 2 + -2j * 2) + -4(4j + -1)
33 + -3j = (14 + -4j) + -4(4j + -1)

Reorder the terms:
33 + -3j = 14 + -4j + -4(-1 + 4j)
33 + -3j = 14 + -4j + (-1 * -4 + 4j * -4)
33 + -3j = 14 + -4j + (4 + -16j)

Reorder the terms:
33 + -3j = 14 + 4 + -4j + -16j

Combine like terms: 14 + 4 = 18
33 + -3j = 18 + -4j + -16j

Combine like terms: -4j + -16j = -20j
33 + -3j = 18 + -20j

Solving
33 + -3j = 18 + -20j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '20j' to each side of the equation.
33 + -3j + 20j = 18 + -20j + 20j

Combine like terms: -3j + 20j = 17j
33 + 17j = 18 + -20j + 20j

Combine like terms: -20j + 20j = 0
33 + 17j = 18 + 0
33 + 17j = 18

Add '-33' to each side of the equation.
33 + -33 + 17j = 18 + -33

Combine like terms: 33 + -33 = 0
0 + 17j = 18 + -33
17j = 18 + -33

Combine like terms: 18 + -33 = -15
17j = -15

Divide each side by '17'.
j = -0.8823529412

Simplifying
j = -0.8823529412

See similar equations:

| 4/21*7/12 | | (w)(2w-1)=91 | | (w)(2w^2)=91 | | 8v^2+10v-3=0 | | x/20-5=-4 | | -4(-5-3x)=116 | | 25x^2+30=55 | | B-24.6=5.1b | | 2+x/4=-2 | | 2(5.5)+3(5.5+1.5)= | | 2(4-20)=8(x-5) | | 6x+52=2x+24 | | B-24.6=5 | | 4p-15=1 | | x/5-7=x+6/3 | | 3+12=9y+4-8y | | 16=x/11 | | 1/x+3/7=5/x | | 5(x+8)=0 | | 7x+3(2x)=39 | | 4(2x-1)-2(3x+5)=x+4 | | 2/3+x^2-5/6+x=0 | | 12+d+8+4d= | | 2/3x^2-5/6x=0 | | 2/3x^2-5/6x | | 5/11x5/12 | | 2(1+5x)=82 | | 24=4x-10 | | 10(r-6)/10r | | -b+2=-.5 | | 5+9x=1+3x | | 6x+3x+x= |

Equations solver categories